Shoot multiplication, essential oils, antioxidant content and antimicrobial activities of Alpinia conchigera Griff. - Radzuan, Raihana (2014)
The research on medicinal value of Alpinia conchigera (Zingiberaceae) in Malaysia have been growing extensively for its antifungal properties. In order to meet the demand for commercial cultivation, the research on the in vitro propagation and the potential of rhizome and leaf oil of this species had been conducted. The whole plant of Alpinia conchigera Griff. (lengkuas padi) were collected from the Conservatory Park, Institute of Bioscience, Universiti Putra Malaysia. This research was divided into two experiments. Experiment 1 involved the establishment of the aseptic cultures of A. conchigera through in vitro propagation for shoot multiplication. The rhizome buds were cultured and directly regenerated in the Murashige and Skoog (MS) medium supplemented with 6-benzylaminopurine (BAP), Kinetin (Kin) at different concentrations (0, 1, 3, 5, 7 mg/L) and naphthalene acetic acid (NAA) at the concentrations of (0.5, 1.0, 1.5 mg/L). The optimum concentration for shoot initiation of A. conchigera was produced in MS medium supplemented with 0.5 mg/L NAA with 3.2 ± 0.9 shoots. Whereas, MS medium supplemented with 1.5 mg/L NAA was optimum for root initiation which gave 16.6 ± 1.4 roots. The effect of adenine on shoot multiplication was also investigated. The highest shoot number was produced in the medium containing 5 mg/L BAP and 0.5 mg/L NAA with the addition of 80 mg/L of adenine with 3.4 ± 0.5 shoot numbers. However, the mediumsupplemented with 80 mg/L adenine alone was observed to give good results for both shoots and roots, therefore was chosen for the rooting stage. Among all the sucrose concentrations, the sucrose supply of 60 g into the medium containing 80 mg/L adenine showed better response of plantlets. Healthy regenerated plantlets were selected for the hardening in a sterile mixture of husk and peat moss with the ratio 1:3. Experiment 2 was conducted to screen the constituents, antioxidant and antimicrobial properties of A. conchigera essential oils. The rhizomes and leaves were subjected to hydrodistillation using Clevenger-type apparatus. Then, the essential oils obtained from each part was analyzed for its volatile constituents by GC-MS analysis. Rhizome oil indicated 38 compounds with major compound detected was eucalyptol (60.58%) whereas the leaf oil produced 51 compounds with the most abundant compound was β-bisabolene (46.70%). The essential oils were then subjected to antioxidant tests namely 2,2-diphenyl-1-1-picrylhydrazyl (DPPH) free radical scavenging activity and β- carotene-linoleic acid assay followed by the total phenolic content (TPC) test. The rhizome oil indicated the highest antioxidant activities and the most abundant phenolic and polyphenolic compounds (IC50=151.7 mg/μl, antioxidant activity=106.01% and TPC=203.3 GAE/100g) followed by leaf oil (IC50=309.8 mg/μl, antioxidant activity=84.96% and TPC=94.1 GAE/100g) when comparing with the synthetic antioxidant, butylated hydroxytoluene (BHT). The antimicrobial assay namely disc diffusion assay and minimum inhibitory concentration (MIC) was conducted against selected microbes. The rhizome oil also showed inhibitory activity against all six bacteria and fungi. In contrast, the leaf oil only showed inhibition against two Gram positive bacteria. Overall, this study had provided the useful evidence on the shoot multiplication of tissue culture plantlets and the essential oils potential of A. conchigera for the its cultivation and commercialization.